Perumusan Strategi Fakultas Teknik Universitas Suryakancana menggunakan Model Gabungan Balanced Scorecard, Sun-Tzu, Quality Function Deployment & Analisis SWOT - Subhan, Ali (Universitas Suryakancana, 2017)
Abstract— The success of a college is influenced by various factors, both internal and external factors of the organization. Faculty of Engineering Suryakancana University is one of the many universities that manage higher education that must be able to survive from various challenges, obstacles and competition with other university institutions. This study aims to formulate the right strategy for Faculty of Engineering Universitas Suryakancana able to compete with the existing universities in Cianjur and in the West Java Province. The method used in this research is by combining several methods among others Balanced Scorecard, Sun-Tzu, Quality Function Deployment, and SWOT Analysis. Based on the result of research there are several formulation of strategy that must be implemented by Faculty of Engineering Suryakancana University, among others the implementation of quality assurance system, improvement of lecturer's resources, strict student selection, sharpening of vision and mission of college, and implementation of internal supervision system.Keywords: SWOT analysis, BSC, QFD, Sun-Tzu Strategy, Strategy Formulation